Occupational Therapy Practice Guidelines for Children and Youth Ages 5-21 Years (Ⅱ) - The American Occupational Therapy Association (康复学报)
In recent years, the literature on activity-and occupation-based interventions that encourage and support maximum participation by children and youth has become increasingly frequent. This practice guide integrates three systematic reviews of activity-and occupation-based interventions for children and youth aged 5-21 years to provide decision guidance and best practice support for their occupational therapy services at home, school and in the community.